THE ROLE OF THE SAT SAMAPTA PATROL OF THE SURAKARTA POLICE TOPREVENT THE OCCURRENCE OF CRIMINAL ACTIONS OF SURPRISE IN THE FRAMEWORK THE CREATION OF HARKAMTIBMAS - TUNGGAL PRATAMA (Police Studies Review, 2022)
The unit for regulation, guard, escort and patrol or the turjagwali unit is one of the Samapta units which has the task of regulating, guarding, escorting and patrolling as well as securing community and government activities , including the prosecution of minor crimes, securing demonstrations, controlling crowds, and securing vital objects as well as animal assistance. The research location in this final project is Polresta Surakarta. There are several problems formulated, including how to carry out the Sat Samapta patrol in preventing criminal acts of stealing and how the supervision and control is carried out so that the patrol can run optimally. The authors aim to explain the implementation of patrol activities and identify supervision and control of patrol activities. The research approach in this final project is qualitative research using field research or research in the field. In order to discuss the formulation of the problem, the author uses an analytical knife in the form of several theories, namely management theory, SWOT analysis theory, and the concept of patrol. The results showed that the implementation of patrol activities and the efforts made by the Turjawali Unit, especially in preventing the crime of theft by weighting in the jurisdiction of the Surakarta Police, were still not optimal. This is due to several factors, including the lack of coordination with other technical functions, the lack of public confidence in the police. Therefore, it is necessary to improve the performance of patrols to prevent criminal acts of theft by weight.